2016
DOI: 10.5507/ag.2015.025
|View full text |Cite
|
Sign up to set email alerts
|

External and internal load of playing positions of elite female handball players (U19) during competitive matches

Abstract: field during either offensive (left wing, left back, centre back, right back, right wing, and pivot) or defensive (players are counted from the side to the centre of the field) phases. Each position has its own specificities. Pivots play in the smallest area (~12 m 2), most of the time between two defenders, wings in ~15 m 2 , while backs and centre backs play in wider spaces (~64 m 2). Tactical roles of each position generate a great deal of body contact and duels (one vs. one confrontation to gain a favourab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 32 publications
2
20
0
5
Order By: Relevance
“…These variables include changes in the intensity of activity as well as motivation. 8 Between the three positions, defenders covered the lowest external workload (10020.4±1086.6 m). Indeed, several studies have previously found defenders to obtain, in general, lower fitness levels, resulting in lower external loads performed in comparison with midfielders and forwards.…”
Section: Conclusion External Workloadmentioning
confidence: 96%
See 2 more Smart Citations
“…These variables include changes in the intensity of activity as well as motivation. 8 Between the three positions, defenders covered the lowest external workload (10020.4±1086.6 m). Indeed, several studies have previously found defenders to obtain, in general, lower fitness levels, resulting in lower external loads performed in comparison with midfielders and forwards.…”
Section: Conclusion External Workloadmentioning
confidence: 96%
“…In football, athletes perform different types of physical movements ranging at a series of intensities. 1,8 Santos et al1 claimed that 80-90% of football spent within a low to moderate intensity zone with 10-20% spent completing high intensity activities. These findings do not match previous research by Jozaket al 24 whom presented 30% of overall football activities to be spent at a high intensity.…”
Section: Heart Rate Of Footballersmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Diğer bir zaman-hareket araştırmasında, 19 yaş altı kadın hentbolcularda koşu mesafeleri yüksek şiddetli koşu ve sprint mesafeleri (oyun kurucular 7.138,3±334.4 m; kanatlar 6.915,3±362,2 m ve pivotlar 6.337,1±477,3 m) literatüre göre yüksek yüzdeye sahip bulunmuştur. 16 Bunun sebebi veri toplanan genç kategori maçlarında rekabetin az olmasıyla (6 resmî müsabakanın 3'ünün 10 sayı üstü fark ile bitmesi) açıklanabilir.…”
Section: Koşu Mesafeleriunclassified
“…Handball is a high-intensity game in which ~80% of each match is played with a workload intensity of over85% of the maximum heart rate 1,2 . Variables affecting this workload include the distance covered and speed, both of which are related to the position played.…”
Section: Introductionmentioning
confidence: 99%